Expert Web Services Security in the .NET Platform - Nantz, Brian (Apress, 2012)
When Microsoft first introduced .NET, the aspect of the technology that garnered the most attention was Web services. On that day, the way that server-side applications were to be written was fundamentally rethought. The concepts of loose coupling, standards-based interfaces, service discovery, and description found their way into the common computer vocabulary.